Metformin use in hidradenitis suppurativa. (2nd April 2020) - Jennings, Lorraine; Hambly, Roisin; Hughes, Rosalind; Moriarty, Blaithin; Kirby, Brian
Abstract: Background: Hidradenitis suppurativa (HS) is a chronic debilitating inflammatory disease, associated with metabolic syndrome, obesity and insulin resistance. Metformin, an oral hypoglycaemic agent, may play an important role in delaying or preventing the onset of diabetes and metabolic syndrome. Metformin has been reported as having efficacy in HS. It may have a role in the treatment of HS and its associated co-morbidities. Objective: To evaluate metformin use, response and tolerability in a HS population. Methods: A retrospective chart review of patients attending a specialist Dermatology HS clinic over 12 months. All patients treated with metformin were included. Results: Fifty-three HS patients received metformin; 85% female; mean age was 37 years and mean weight was 102 kg. The mean duration of metformin was 11.3 months and mean dose was 1.5 g/days. The 6- and 12-month drug survival were 61% and 39%, respectively. Metformin was well tolerated. Gastrointestinal side effects were experienced by 11%. Subjective clinical response was seen in 68% ( n  = 36) with 19% (7/36) of these having quiescent disease with metformin monotherapy. 25% had no improvement. Insulin resistance was seen in 75%. Its presence did not predict clinical response to metformin. Conclusion: Metformin is an effective, well tolerated and inexpensive treatment that represents a viable treatment option for HS. Key message: Metformin is an effective; well tolerated and inexpensive treatment in the management of HS.